2016
DOI: 10.1111/1744-9987.12450
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Endovascular Therapy and Low‐Density Lipoprotein Apheresis Combined Treatment in Hemodialysis Patients With Critical Limb Ischemia due to Below‐Knee Arterial Lesions

Abstract: To assess the clinical benefit of combined treatment of below-knee endovascular therapy (BK-EVT) plus low-density lipoprotein apheresis (LDLA) compared with BK-EVT monotherapy, we retrospectively evaluated the clinical outcome of hemodialysis (HD) patients with critical limb ischemia (CLI) due to isolated BK arterial lesions who underwent BK-EVT or BK-EVT plus short-term LDLA. Between October 2011 and September 2014, 62 HD patients underwent isolated BK-EVT monotherapy (BK-EVT group), and 25 HD patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Nutritional status was also shown to be related to the mortality of hemodialysis patients, with malnutrition increasing the mortality of patients. NRS2002 scale was used in this study to assess the nutritional status; other scales used in previous research have also indicated a relationship between malnutrition and mortality in hemodialysis patients (18). CRP contributed to the mortality of included patients in our study and has been identified as an important risk factor of mortality in hemodialysis patients in previous work (15,24).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Nutritional status was also shown to be related to the mortality of hemodialysis patients, with malnutrition increasing the mortality of patients. NRS2002 scale was used in this study to assess the nutritional status; other scales used in previous research have also indicated a relationship between malnutrition and mortality in hemodialysis patients (18). CRP contributed to the mortality of included patients in our study and has been identified as an important risk factor of mortality in hemodialysis patients in previous work (15,24).…”
Section: Discussionmentioning
confidence: 57%
“…Some effort has been made to further improve the effectiveness of EVT in hemodialysis patients. Ohtake et al attempted to combine EVT with low-density lipoprotein apheresis to treat critical limb ischemia (18). Their findings indicated that the cumulative rate of major adverse limb events was significantly improved in the combined group compared to the EVT group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoprotein apheresis has also shown promising results in treatment of nephropathy in diabetes mellitus and nephrotic syndrome of various etiologies . It has been suggested that lipoprotein apheresis can reduce the risk of in‐stent coronary restenosis in the early postimplantation period, and also have favorable effects in patients with critical limb ischemia due to below‐knee arterial lesions . In these studies, double filtration plasmapheresis, dextran sulfate plasma adsorption, and heparin‐induced, extracorporeal LDL precipitation were used as lipoprotein apheresis systems.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 For these patients, additional conservative therapies, such as low-density lipoprotein apheresis, hyperbaric oxygen therapy, and spinal cord stimulation were administered. 9-14 However, they were not effective in several cases. In contrast, some reports indicated that nitrate patch is useful therapy for patients with PAD.…”
mentioning
confidence: 99%